Front Matter Jurnal Litbang Industri Vol. 7 No. 2 Desember Tahun 2017 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2017)
Front Matter Jurnal Litbang Industri Vol. 7 No. 2 Desember Tahun 2017